Method for producing hollow resin particles

Through suspension polymerization and solid-liquid separation technology, hollow resin particles with high void ratio and excellent heat resistance are prepared, which solves the problems of low void ratio and poor productivity in the prior art, and achieves more efficient manufacturing and application performance.

CN115785516BActive Publication Date: 2025-04-11ZEON CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202211665357.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-01-31
Filing Date
2018-07-31
Publication Date
2025-04-11
Estimated Expiration
2038-07-31

AI Technical Summary

Technical Problem

The prior art is difficult to meet the conditions of high void ratio and stable manufacturing at the same time, resulting in the problems of low void ratio, poor productivity and poor heat resistance in their applications.

Method used

By using an oil-soluble polymerization initiator through the suspension polymerization method, a copolymer containing hydrophilic monomer units was prepared to react with the alkali to produce alkali swelling, the void ratio of the latex particles was controlled, and solid-liquid separation was performed and the hydrocarbon-based solvent was removed after polymerization, and hollow resin particles with high void ratio and excellent heat resistance were obtained.

Benefits of technology

It achieves higher void ratio and better heat resistance than the prior art, and improves the production efficiency and application performance of hollow resin particles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115785516B_ABST
    Figure CN115785516B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for producing hollow resin particles, characterized in that the method comprises the steps of preparing a mixed solution, preparing a suspension, preparing a precursor composition containing precursor particles, performing solid-liquid separation to obtain precursor particles, and removing an enclosed hydrocarbon solvent to obtain hollow resin particles having a porosity of 74% to 99%. The method for producing hollow resin particles of the present invention can produce hollow resin particles having a higher porosity than the prior art and excellent heat resistance with high productivity.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application number 201880050093.5. The application date of the original application is July 31, 2018, and the name of the invention is "Method for manufacturing latex and method for manufacturing hollow resin particles". Technical Field

[0002] The present invention relates to a method for producing hollow resin particles having a higher porosity than that of the prior art. Background Art

[0003] Compared with resin particles with substantially no voids inside, hollow resin particles can scatter light well and reduce light transmittance. Therefore, they can be widely used in water-based coatings, paper coating compositions, and the like as organic pigments and masking agents with excellent optical properties such as opacity and whiteness.

[0004] Here, in the use of water-based coatings, paper coating compositions, etc., in order to improve the effects of lightweighting, heat insulation, and opacification of coatings, paper coating compositions, etc., it is desired to increase the porosity of the formulated hollow resin particles. However, in the existing known production methods, it is difficult to satisfy the production conditions that can obtain the desired physical properties and stably produce hollow resin particles with a high porosity.

[0005] For example, Patent Document 1 discloses the following technology: an emulsion containing a hydrophilic core polymer, a first shell polymer and a second shell polymer is polymerized to form multistage polymer particles, and the formed multistage polymer particles are neutralized with a base to swell the hydrophilic core polymer, thereby forming particles having voids.

[0006] In addition, Patent Document 2 discloses the following technology: a polymerizable monomer component is dispersed in an aqueous dispersion medium in the presence of different polymer microparticles having different compositions, the different polymer microparticles are allowed to absorb the above-mentioned polymerizable monomer component, and then the above-mentioned polymerizable monomer component is polymerized. The document states as follows: in the aqueous dispersion medium, in addition to the polymerizable monomer component, different polymers are allowed to coexist with it in the form of microparticles or solutions; therefore, during polymerization, a core is formed in the dispersed particles due to phase separation of the different polymers, and a certain polymer undergoes polymerization shrinkage while the core is generated; as a result, pores are formed inside the polymer.

[0007] In addition, Patent Document 3 discloses a method for producing hollow polymer particles, characterized in that a base is added to a latex containing polymer particles so that the pH of the latex is above 8, and then an acid is added so that the pH of the latex is below 7, the polymer particles having at least a three-layer structure comprising a central layer polymer, an intermediate layer polymer and a surface layer polymer, the central layer polymer being obtained by copolymerizing a monomer mixture of 20 to 60 mass % of a carboxyl group-containing monomer and 80 to 40 mass % of a monomer capable of copolymerizing therewith, the intermediate layer polymer being obtained by copolymerizing a monomer mixture of 1 to 12 mass % of a carboxyl group-containing monomer and 99 to 88 mass % of a monomer capable of copolymerizing therewith, and the surface layer polymer being obtained by polymerizing a monomer that does not contain a carboxyl group.

[0008] In addition, patent documentation 4 discloses a kind of manufacture method of heat-expandable microsphere, and this heat-expandable microsphere is made of the shell formed by thermoplastic resin as essential component and the whipping agent that is coated in the shell as essential component.Have on record in this document, can stably manufacture the heat-expandable microsphere with the mean particle size of regulation with good yield when not making expansion performance variation.

[0009] In addition, Patent Document 5 discloses as follows: When manufacturing hollow resin particles, (1) a dispersed phase is prepared, which includes a vinyl monomer without a nitrile group, a phase separation promoter, a volatile solvent, a polymerization initiator, and a reaction catalyst, (2) a continuous phase is prepared, which includes a solvent and a surfactant, (3) after adding the dispersed phase to the continuous phase, the obtained mixture is stirred, (4) the obtained aqueous dispersion is supplied to a polymerization reaction under pressure, (5) the mixture after the polymerization reaction is decompressed at a temperature above the boiling point of the volatile solvent to obtain an aqueous dispersion, (6) the obtained aqueous dispersion is filtered and dried to obtain hollow resin particles. The document states that since the resin constituting the shell of the hollow resin particles is formed by a vinyl monomer without a nitrile group, the nitrile group will not be detached even at high temperatures, and the strength of the shell is not easily reduced.

[0010] Patent Document 6 discloses a method for producing hollow polymer particles by polymerizing a dispersion of a hydrophilic monomer, a crosslinking monomer, and other monomers that coexist with an oily substance, and then removing the oily substance in the particles in a liquid phase or a gas phase.

[0011] Patent Document 7 discloses a method for producing hollow particles in which the organic solvent contained in the fine particles is removed in an aqueous medium to cause hollowing and thereby suppress collapse.

[0012] Patent Document 8 discloses hollow polymer fine particles containing a high content of a cross-linkable monomer.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent document 1: Japanese Patent Application Publication No. 11-349839;

[0016] Patent document 2: Japanese Patent Application Publication No. 62-127336;

[0017] Patent document 3: Japanese Patent Application Publication No. 6-248012;

[0018] Patent Document 4: International Publication No. 2017 / 002659;

[0019] Patent Document 5: Japanese Patent Application Publication No. 2008-231241;

[0020] Patent document 6: Japanese Patent Application Publication No. 61-87734;

[0021] Patent Document 7: Japanese Patent Application Publication No. 2013-221070;

[0022] Patent document 8: Japanese Patent Application Publication No. 2002-80503.

[0023] Problem that the invention aims to solve

[0024] However, Patent Document 1 does not describe the evaluation of the void ratio of multistage polymer particles.

[0025] Patent Document 2 also describes that polymer particles having inner pores can be easily produced. However, the polymer particles described in Patent Document 2 have a problem of low porosity.

[0026] Patent document 3 records the manufacture of hollow polymer particles with a shell thickness of less than 50 nm and a large porosity. However, the porosity of the hollow polymer particles actually disclosed in the examples of patent document 3 is still around 70%. In addition, the method described in patent document 3 has the problem of poor productivity.

[0027] Patent documentation 4 has been put down in writing, from the aspect of expansion performance, preferably comprising nitrile monomer as essential component. However, the resin particles comprising nitrile monomer usually have poor heat resistance. In addition, the technology of patent documentation 4 also has the following problem, because the foaming of whipping agent and utilizing thermal expansion reaction to expand microsphere, it is difficult to accurately control the particle diameter of microsphere.

[0028] In addition, Patent Document 5 describes that hollow resin particles are formed by decompressing the particles at a temperature above the boiling point of the volatile solvent, thereby utilizing the pressure of the volatile solvent contained therein when it evaporates to push out the resin. However, since the particles are expanded by reducing the pressure while applying heat to the particles, there is a problem that the particle size of the obtained hollow resin particles is not uniform.

[0029] The technology of Patent Document 6 has the following problem: when the amount of oily substance is increased to produce hollow particles with a thin shell thickness, the particles are damaged when the oily substance is removed due to the low strength of the shell, and particles with a high porosity cannot be obtained.

[0030] The hollow particles produced by the method described in Patent Document 7 contain water, and when used for applications such as heat insulating agents, a process of removing the water inside is required. At this stage, there is a problem that the particles collapse and the porosity decreases.

[0031] When the ratio of the crosslinkable monomer is high as in the hollow polymer fine particles described in Patent Document 8, a high-temperature and long-time treatment is required to remove the hydrocarbons inside, which leads to a problem of poor productivity. Summary of the invention

[0032] An object of the present invention is to provide a method for producing a latex containing hollow resin particles having a higher porosity than that of the prior art, and to provide a method for producing hollow resin particles having a higher porosity than that of the prior art.

[0033] Solutions for solving problems

[0034] The present inventors have focused on the use of an oil-soluble polymerization initiator in a method for obtaining a latex containing latex particles having a hollow portion by suspension polymerization. In addition, the present inventors have focused on the reaction of a copolymer containing a hydrophilic monomer unit with an alkali to produce alkali swelling. Based on these viewpoints, the present inventors have found that by using a dispersion obtained by dispersing an appropriate material in an aqueous medium, the porosity of the latex particles in the obtained latex can be controlled to be larger than the porosity of the prior art.

[0035] In addition, the inventors of the present invention have focused on the fact that in order to maintain a hollow spherical shape with a high porosity in a method of obtaining hollow resin particles by suspension polymerization, post-treatment after the polymerization reaction is particularly important. Furthermore, in order to improve the heat resistance of the hollow resin particles, the inventors of the present invention have studied the types of polymers constituting the hollow resin particles. As a result, the inventors of the present invention have found that by using specific monomers during polymerization and performing solid-liquid separation after polymerization, hollow resin particles with a higher porosity and excellent heat resistance than the prior art can be obtained.

[0036] That is, the first production method of the present invention is a method for producing latex, characterized in that it is a method for producing latex containing latex particles having a hollow portion, comprising the following steps:

[0037] A step of preparing a mixed solution, wherein the mixed solution comprises at least one monomer selected from a monovinyl monomer and a hydrophilic monomer, a crosslinking monomer, an oil-soluble polymerization initiator, a fat, a hydrocarbon solvent, a suspension stabilizer, and an aqueous medium;

[0038] A step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the mixed solution;

[0039] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion and containing a hydrocarbon solvent;

[0040] A step of adding a base to the precursor composition to adjust the pH of the precursor composition to 6.0 or higher; and

[0041] A step of obtaining a latex containing latex particles having a hollow portion by removing the hydrocarbon solvent contained in the precursor particles in the precursor composition.

[0042] In the first production method of the present invention, one or more of the above-mentioned monovinyl monomers and one or more of the above-mentioned hydrophilic monomers may be used in combination.

[0043] In the first production method of the present invention, when the total mass of the one or more monovinyl monomers and the one or more hydrophilic monomers is taken as 100 mass %, the total mass ratio of the one or more hydrophilic monomers may be 10 to 50 mass %.

[0044] In the first production method of the present invention, the number average particle size of the latex particles contained in the obtained latex may be 0.1 to 10 μm.

[0045] In the first production method of the present invention, the porosity of the latex particles contained in the obtained latex may be 70 to 99%.

[0046] The second production method of the present invention is a method for producing hollow resin particles, which is characterized by comprising the following steps:

[0047] A step of preparing a mixed solution, wherein the mixed solution comprises at least one monomer selected from a monovinyl monomer and a hydrophilic monomer (excluding acrylonitrile and methacrylonitrile), a crosslinking monomer, an oil-soluble polymerization initiator, a hydrocarbon solvent, a suspension stabilizer, and an aqueous medium, and the content of the crosslinking monomer is 25 to 59 parts by mass when the total mass of the at least one monomer selected from a monovinyl monomer and a hydrophilic monomer and the crosslinking monomer is taken as 100 parts by mass;

[0048] A step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the mixed solution;

[0049] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion and containing a hydrocarbon solvent;

[0050] A step of obtaining the precursor particles by subjecting the precursor composition to solid-liquid separation; and

[0051] A step of obtaining hollow resin particles by removing the hydrocarbon solvent contained in the precursor particles in a gas phase.

[0052] In the second production method of the present invention, the monovinyl monomer may be at least one selected from acrylic acid esters and methacrylic acid esters, and the hydrophilic monomer may be at least one selected from acrylic acid and methacrylic acid.

[0053] In the second production method of the present invention, the method for separating the precursor composition into solid and liquid may be a centrifugal method or a filtration method.

[0054] In the second manufacturing method of the present invention, the process of preparing the above-mentioned mixed liquid can be a process of mixing an oil phase and an aqueous phase, the above-mentioned oil phase contains at least one monomer selected from the monovinyl monomer and the hydrophilic monomer, a cross-linking monomer, an oil-soluble polymerization initiator and a hydrocarbon solvent, and when the total mass of the at least one monomer selected from the monovinyl monomer and the hydrophilic monomer and the cross-linking monomer is taken as 100 parts by mass, the content of the cross-linking monomer is 25 to 59 parts by mass, and the above-mentioned aqueous phase contains the above-mentioned suspension stabilizer and an aqueous medium.

[0055] In the second production method of the present invention, the hydrocarbon solvent may have a relative dielectric constant of 3 or less at 20°C.

[0056] In the second production method of the present invention, the hydrocarbon solvent may be a hydrocarbon compound having 5 to 7 carbon atoms.

[0057] In the second production method of the present invention, the hydrocarbon solvent may be contained in an amount of 200 parts by mass or more based on 100 parts by mass of the total mass of the at least one monomer selected from the monovinyl monomer and the hydrophilic monomer and the crosslinking monomer.

[0058] In the second production method of the present invention, the number average particle size of the hollow resin particles obtained may be 0.1 to 10 μm.

[0059] In the second production method of the present invention, the void ratio of the obtained hollow resin particles may be 70 to 99%.

[0060] Effects of the Invention

[0061] As described above, according to the first production method of the present invention, latex containing latex particles having a higher porosity than in the related art can be efficiently produced.

[0062] As described above, according to the second manufacturing method of the present invention, since a polymer containing monomer units derived from a monovinyl monomer and / or a hydrophilic monomer is polymerized, and the obtained precursor composition is subjected to solid-liquid separation after the polymerization, and then the hydrocarbon solvent is removed from the precursor particles, it is possible to manufacture hollow resin particles having a higher porosity and excellent heat resistance than the prior art with high productivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 This is a schematic diagram showing an example of the first production method (production method of latex) of the present invention.

[0064] Figure 2 This is a schematic diagram showing an example of the second production method (the production method of hollow resin particles) of the present invention.

[0065] Figure 3 The figure is a schematic diagram showing one embodiment of the suspension in the suspension preparation process.

[0066] FIG. 4A is a SEM image of the hollow resin particles of Example II-1.

[0067] FIG. 4B is a SEM image of a cross section of the hollow resin particles of Example II-1.

[0068] Figure 5 This is a schematic diagram showing a conventional dispersion liquid for emulsion polymerization.

[0069] FIG. 6A is a schematic diagram of a conventional core resin particle.

[0070] FIG. 6B is a schematic cross-sectional view of a conventional core-shell resin particle.

[0071] FIG. 6C is a schematic cross-sectional view of a conventional hollow resin particle. DETAILED DESCRIPTION

[0072] Hereinafter, in the present invention, "hollow" refers to a state in which at least one selected from a liquid portion, a gas portion, and a mixed portion of liquid and gas can be confirmed to exist inside the particle by a common observation method. In the present invention, a "liquid portion" refers to a continuous portion filled with liquid. In the present invention, a "gas portion" refers to a continuous portion filled with gas. In the present invention, a "mixed portion of liquid and gas" refers to a continuous portion filled with liquid and gas.

[0073] In the present invention, "hollow portion" refers to the portion of the particle occupied by the hollow space. Whether a particle has a hollow portion can be confirmed by, for example, observing a cross section of the particle under SEM or directly observing the particle under TEM.

[0074] The shell of the resin in the particle may not have continuous pores, and the "hollow portion" in the present invention is isolated from the outside of the particle by the shell of the particle.

[0075] The shell portion of the resin in the particle may have one or more communicating holes, and the "hollow portion" in the present invention is connected to the outside of the particle via the communicating holes.

[0076] In the present invention, "precursor particles" refer to particles whose hollow parts are filled with water or a mixture of water and gas, or an aqueous medium or a mixture of an aqueous medium and gas. In the present invention, "precursor composition" refers to a composition containing precursor particles.

[0077] In the present invention, "latex particles having a hollow portion" refers to particles having a hollow portion among particles contained in latex.

[0078] In the present invention, "hollow resin particles" refer to resin particles whose hollow parts are filled with gas.

[0079] The first production method of the present invention is a method for producing latex, characterized in that it is a method for producing latex containing latex particles having a hollow portion, comprising the following steps:

[0080] A step of preparing a mixed solution, wherein the mixed solution comprises at least one monomer selected from a monovinyl monomer and a hydrophilic monomer, a crosslinking monomer, an oil-soluble polymerization initiator, a fat, a hydrocarbon solvent, a suspension stabilizer, and an aqueous medium;

[0081] A step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the mixed solution;

[0082] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion and containing a hydrocarbon solvent;

[0083] A step of adding a base to the precursor composition to adjust the pH of the precursor composition to 6.0 or higher; and

[0084] A step of obtaining a latex containing latex particles having a hollow portion by removing the hydrocarbon solvent contained in the precursor particles in the precursor composition.

[0085] The second production method of the present invention is a method for producing hollow resin particles, which is characterized by comprising the following steps:

[0086] A step of preparing a mixed solution, wherein the mixed solution comprises at least one monomer selected from a monovinyl monomer and a hydrophilic monomer (excluding acrylonitrile and methacrylonitrile), a crosslinking monomer, an oil-soluble polymerization initiator, a hydrocarbon solvent, a suspension stabilizer, and an aqueous medium, and the content of the crosslinking monomer is 25 to 59 parts by mass when the total mass of the at least one monomer selected from a monovinyl monomer and a hydrophilic monomer and the crosslinking monomer is taken as 100 parts by mass;

[0087] A step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the mixed solution;

[0088] A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion and containing a hydrocarbon solvent;

[0089] A step of obtaining the precursor particles by subjecting the precursor composition to solid-liquid separation; and

[0090] A step of obtaining hollow resin particles by removing the hydrocarbon solvent contained in the precursor particles in a gas phase.

[0091] The first production method and the second production method of the present invention are common in that a mixed solution containing common raw materials is suspended and the obtained suspension is supplied to a polymerization reaction. The first production method and the second production method are described in sequence below. The description of the second production method is only for the points that are different from the first production method in principle unless otherwise specified.

[0092] 1. First Manufacturing Method

[0093] The first production method of the present invention comprises (1) a mixed solution preparation step, (2) a suspension preparation step, (3) a polymerization step, (4) a base addition step, and (5) a solvent removal step. The production method of the present invention is not limited to these five steps.

[0094] Figure 1 This is a schematic diagram showing an example of the first production method of the present invention. Figure 1 (1) to (5) in the figure correspond to the above steps (1) to (5). The white arrows between the figures indicate the order of the steps. Figure 1 and the following Figure 2 These are schematic diagrams for explanation only, and the manufacturing method of the present invention is not limited to the contents shown in these figures. In addition, the structure, size and shape of the materials used in each manufacturing method of the present invention are not limited to the structure, size and shape of the various materials in these figures.

[0095] Figure 1 (1) is a cross-sectional schematic diagram showing an embodiment of a mixed solution in a mixed solution preparation process. As shown in the figure, the mixed solution includes an aqueous medium 1 and a low-polarity material 2 dispersed in the aqueous medium 1. Here, the low-polarity material 2 refers to a material with low polarity and difficult to mix with the aqueous medium 1, such as a hydrocarbon solvent.

[0096] Figure 1 (2) is a schematic cross-sectional view showing an embodiment of a suspension in the suspension preparation process. The suspension includes an aqueous medium 1 and micelles 10 (monomer droplets) dispersed in the aqueous medium 1. The micelles 10 are composed of a suspension stabilizer 3 (such as a surfactant, etc.) surrounding an oil-soluble monomer composition 4 (including an oil-soluble polymerization initiator 5, etc.).

[0097] Figure 1 (3) is a schematic cross-sectional view showing an embodiment of a precursor composition after the polymerization step. The precursor composition includes an aqueous medium 1 and precursor particles 20 dispersed in the aqueous medium 1. The shell 6 located outside the precursor particles 20 is formed by polymerization of the monomers in the micelle 10. The hollow portion inside the shell 6 contains a hydrocarbon solvent 7. The shell 6 contains fat 13.

[0098] Figure 1 (4) is a schematic cross-sectional view showing an embodiment of the precursor composition after the alkali addition step. By adding the alkali, the fat is dissolved into the external aqueous medium 1, forming the shell defect 14. As a result, the hollow portion of the precursor particle 20 is connected to the outside of the precursor particle 20 via the shell defect 14. In addition, the principle of removing fat from the precursor particle 20 will be described later.

[0099] Figure 1(5) is a schematic cross-sectional view showing an embodiment of the latex after the solvent removal step. (5) This figure shows a state where the hydrocarbon solvent 7 is removed from the precursor particles 20 in (4) above. As a result, a latex 100B is obtained, which includes latex particles 100A, and the latex particles 100A have a hollow portion 8 inside the shell portion 6. The aqueous medium 1 is removed from the latex 100B, and the hollow portion of the obtained latex particles 100A is replaced with a gas to obtain hollow resin particles.

[0100] Hereinafter, the above-mentioned five steps and other steps will be described in sequence.

[0101] (1) Mixed solution preparation process

[0102] This step is a step of preparing a mixed solution, which contains (A) at least one monomer selected from a monovinyl monomer and a hydrophilic monomer, (B) a cross-linking monomer, (C) an oil-soluble polymerization initiator, (D) oils and fats, (E) a hydrocarbon solvent, (F) a suspension stabilizer, and (G) an aqueous medium.

[0103] (A) at least one monomer selected from monovinyl monomers and hydrophilic monomers

[0104] In the present invention, monomer refers to a compound having one functional group capable of polymerization. As a monomer, only a monovinyl monomer can be used, only a hydrophilic monomer can be used, or a monovinyl monomer and a hydrophilic monomer can be used in combination. By polymerization of monomers, a polymer or oligomer is generated. In addition, in the present invention, unless otherwise specified, "at least one monomer selected from a monovinyl monomer and a hydrophilic monomer" does not include "crosslinking monomer" described later. In addition, in the present invention, sometimes "at least one monomer selected from a monovinyl monomer and a hydrophilic monomer" is recorded as "(A) monomer".

[0105] In the present invention, the monovinyl monomer refers to a compound having one polymerizable vinyl functional group, and is a compound other than the hydrophilic monomer described below.

[0106] In the present invention, examples of the monovinyl monomer include at least one acrylic monovinyl monomer selected from acrylic acid esters and methacrylic acid esters; aromatic vinyl monomers such as styrene, vinyl toluene, α-methylstyrene, p-methylstyrene, and halogenated styrene; monoolefin monomers such as ethylene, propylene, and butene; (meth)acrylamide monomers such as (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide, and their derivatives; diene monomers such as butadiene and isoprene; carboxylic acid vinyl ester monomers such as vinyl acetate; halogenated vinyl monomers such as vinyl chloride; halogenated vinyl monomers such as vinylidene chloride; vinylpyridine monomers, etc. The monovinyl monomer may be at least one acrylic monovinyl monomer selected from acrylic acid esters and methacrylic acid esters.

[0107] Examples of the acrylic monovinyl monomer include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, glycidyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc. In the present invention, (meth)acrylate refers to acrylate and / or methacrylate.

[0108] Among the acrylic monovinyl monomers, it is preferred to use at least one selected from butyl acrylate and methyl methacrylate.

[0109] These monovinyl monomers can be used alone or in combination of two or more.

[0110] In the present invention, the hydrophilic monomer refers to a compound soluble in water, and more specifically, a compound having a solubility in water of 1% by mass or more. It is preferred that the hydrophilic monomer is supplied to the polymerization because the amount of aggregates in the obtained latex can be suppressed to a small extent.

[0111] In the present invention, examples of the hydrophilic monomer include acid group-containing monomers, hydroxyl group-containing monomers, amide group-containing monomers, and polyoxyethylene group-containing monomers.

[0112] The acid group-containing monomer in the present invention refers to a monomer containing an acid group. The acid group mentioned here includes any one of a proton-donating group (Brønsted acid group) and an electron pair accepting group (Lewis acid group). When the acid group-containing monomer is used as a hydrophilic monomer, hollow resin particles with high heat resistance can be obtained, and from this point of view, it is preferred.

[0113] The acid group-containing monomer is not particularly limited as long as it has an acid group, and examples thereof include: ethylenically unsaturated carboxylic acid monomers such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, fumaric acid, maleic acid, butenyl tricarboxylic acid, etc.; carboxyl group-containing monomers such as monoalkyl esters of unsaturated dicarboxylic acids such as monoethyl itaconate, monobutyl fumarate, and monobutyl maleate; and sulfonic acid group-containing monomers such as styrene sulfonic acid. Among the acid group-containing monomers, it is particularly preferred to use ethylenically unsaturated carboxylic acid monomers, more preferably at least one acrylic hydrophilic monomer selected from acrylic acid and methacrylic acid, and a maleic acid monomer, and further preferably an acrylic hydrophilic monomer. When an acrylic hydrophilic monomer ((meth)acrylic acid) and the above-mentioned acrylic monovinyl monomer ((meth)acrylate) are used in combination, the preferred mass ratio is (meth)acrylic acid: (meth)acrylate = 100:0 to 30:70, and the more preferred mass ratio is (meth)acrylic acid: (meth)acrylate = 95:5 to 35:65. Compared with the case of using a monomer having a nitrile group, the heat resistance of the obtained hollow resin particles can be improved by using a relatively high temperature resistant monomer such as (meth)acrylic acid and the above-mentioned (meth)acrylate in this manner. In addition, in the present invention, (meth)acrylic acid refers to acrylic acid and / or methacrylic acid.

[0114] When a hydroxyl-containing monomer is used as a hydrophilic monomer, it is preferred because the amount of coagulation in the obtained latex can be suppressed to be small. Examples of the hydroxyl-containing monomer include 2-hydroxyethyl acrylate monomer, 2-hydroxyethyl methacrylate monomer, 2-hydroxypropyl acrylate monomer, 2-hydroxypropyl methacrylate monomer, and 4-hydroxybutyl acrylate monomer.

[0115] Examples of the amide group-containing monomer include acrylamide monomers and dimethylacrylamide monomers.

[0116] Examples of the polyoxyethylene group-containing monomer include methoxy polyethylene glycol acrylate monomers and methoxy polyethylene glycol methacrylate monomers.

[0117] These hydrophilic monomers can be used alone or in combination of two or more.

[0118] In the first production method, one or more monovinyl monomers and one or more hydrophilic monomers may be used in combination. The reason is as follows.

[0119] 6A to 6C show various stages of a conventional hollow resin particle manufacturing process. Fig. 6A is a schematic diagram of a core resin particle 61. Fig. 6B is a cross-sectional schematic diagram of a core-shell resin particle 200B. Fig. 6C is a cross-sectional schematic diagram of a hollow resin particle 200C.

[0120] In the prior art, a core resin particle 61 (FIG. 6A) containing an alkali-swellable substance is formed inside, and a shell 62 (FIG. 6B) is formed outside the core resin particle 61. By utilizing the swelling of the core resin particle 61 caused by the addition of alkali, a three-layer hollow resin particle 200C (FIG. 6C) including a hollow portion 64, a hollow core 63, and a shell 62 is manufactured. However, the void ratio of the hollow resin particle manufactured by this method is low, being 55% or less.

[0121] In a preferred embodiment of the first production method, by using a monovinyl monomer and a hydrophilic monomer in combination, the shell of the hollow resin particles can be swelled in the base addition step described later, making it easy to remove the hydrocarbon solvent, and the porosity of the obtained hollow resin particles can be further improved compared with the prior art.

[0122] When the total mass of the above-mentioned materials (A) to (F) is taken as 100 mass %, the mass ratio of the (A) monomer is preferably 5 to 50 mass %, and more preferably 10 to 40 mass %. When the mass ratio of the (A) monomer is 5 to 50 mass %, the mechanical properties of the hollow resin particles can be further improved than those of the prior art while maintaining the hollowness of the hollow resin particles in the obtained latex, and the porosity of the hollow resin particles can be further improved than those of the prior art.

[0123] When the total mass of the above-mentioned one or more monovinyl monomers and the above-mentioned one or more hydrophilic monomers is taken as 100 mass %, the total mass ratio of the above-mentioned one or more hydrophilic monomers is preferably 10 to 50 mass %, and more preferably 15 to 40 mass %. When the above-mentioned total mass ratio of the above-mentioned one or more hydrophilic monomers is 10 to 50 mass %, in the alkali addition step described later, the alkali is more easily permeated into the particles, the hollow part in the particles is easily and quickly formed, and further, the copolymerization reaction of the above-mentioned monovinyl monomer and the hydrophilic monomer is easily and stably carried out.

[0124] (B) Crosslinking Monomer

[0125] In the present invention, a crosslinkable monomer refers to a compound having two or more polymerizable functional groups. By using a crosslinkable monomer, the mechanical properties of the shell of the obtained hollow resin particles can be improved. In addition, since there are multiple polymerizable functional groups, the above-mentioned (A) monomers can be linked to each other, and the dissolution of hydrophilic monomers (especially acid group-containing monomers) to the outside of the hollow resin particles can be suppressed, and the heat resistance of the obtained hollow resin particles can be improved.

[0126] As a crosslinking monomer, there is no particular limitation as long as it has two or more polymerizable functional groups. Examples of the crosslinking monomer include divinylbenzene, diallyl phthalate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, etc. Among them, divinylbenzene and ethylene glycol di(meth)acrylate are preferred.

[0127] When the total mass of the (A) monomer and the (B) crosslinkable monomer is 100 parts by mass, the content of the (B) crosslinkable monomer is preferably 1 to 59 parts by mass, more preferably 3 to 57 parts by mass, and even more preferably 5 to 55 parts by mass. When the content of the (B) crosslinkable monomer is 1 to 59 parts by mass, the risk of the obtained hollow resin particles being sunken is low, so the porosity of the hollow resin particles can be maintained high, and the risk of a large amount of hydrocarbon solvent remaining in the hollow resin particles is also low.

[0128] In addition, the mixed liquid may contain other polymerizable monomers in addition to the (A) monomer and the (B) crosslinkable monomer.

[0129] (C) Oil-soluble polymerization initiator

[0130] In the present invention, the emulsion polymerization method using a water-soluble polymerization initiator is not used, but the suspension polymerization method using an oil-soluble polymerization initiator is used. The advantages of using the suspension polymerization method will be described in detail in "(2) Suspension Preparation Step".

[0131] The oil-soluble polymerization initiator is not particularly limited as long as it is a lipophilic oil-soluble polymerization initiator having a solubility in water of 0.2 mass % or less. Examples of the oil-soluble polymerization initiator include benzoyl peroxide, dodecanoyl peroxide, tert-butyl 2-ethylperoxyhexanoate, 2,2'-azobis(2,4-dimethylvaleronitrile), and azobisisobutyronitrile.

[0132] When the total mass of the (A) monomer and the (B) crosslinkable monomer is 100 parts by mass, the content of the (C) oil-soluble polymerization initiator is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 7 parts by mass, and further preferably 1 to 5 parts by mass. When the above content of the oil-soluble polymerization initiator is 0.1 to 10 parts by mass, the polymerization reaction can be fully carried out, and the risk of the oil-soluble polymerization initiator remaining after the polymerization reaction is completed is small, and the risk of unexpected side reactions is also small.

[0133] (D) Grease

[0134] The fat or oil in the present invention is not particularly limited as long as it is a lipophilic fat or oil having a solubility in water of 0.2% by mass or less, and any of vegetable oils, animal oils, and synthetic oils can be used.

[0135] like Figure 1 As shown in (3), due to its polarity, the fat 13 is entirely or partially offset in the shell 6. When an alkali is added to the precursor composition containing the precursor particles 20 in this state, the fat 13 is saponified (hydrolyzed), and as a result, the fatty acids and glycerol constituting the fat 13 are eluted into the external aqueous medium 1, forming the shell defects 14 ( Figure 1 (4)). Thus, the inside and outside of the precursor particle 20 are connected.

[0136] Furthermore, the volume occupied by the fat 13 decreases due to the saponification (hydrolysis) of the fat 13, and the porosity of the obtained hollow resin particles increases. The porosity of the hollow resin particles can be controlled by adjusting the type and amount of fat added.

[0137] Examples of the fats and oils include linoleic oil, lard, olive oil, coconut oil, castor oil, cottonseed oil, and the like.

[0138] When the total mass of the (A) monomer and the (B) crosslinkable monomer is taken as 100 parts by mass, the content of the (D) fat is preferably 1 to 20 parts by mass, more preferably 2 to 15 parts by mass, and further preferably 5 to 12 parts by mass. When the above-mentioned content of the fat is 1 to 20 parts by mass, an appropriate number of shell defects can be formed in the hollow resin particles in the obtained latex, as a result, the removal of the hydrocarbon solvent in the hollow resin particles can be facilitated, and the mechanical properties of the hollow resin particles can be improved while maintaining the hollowness.

[0139] (E) Hydrocarbon solvent

[0140] The hydrocarbon solvent in the present invention has a function of forming a hollow portion inside the particles.

[0141] In the suspension preparation step described later, a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium can be obtained. In the suspension preparation step, phase separation occurs in the monomer droplets, and as a result, the hydrocarbon solvent with low polarity tends to gather inside the monomer droplets. Finally, in the monomer droplets, the hydrocarbon solvent is distributed inside the monomer droplets according to their respective polarities, and other materials except the hydrocarbon solvent are distributed on the periphery of the monomer droplets.

[0142] Then, in the polymerization step described below, a precursor composition including precursor particles enclosing a hydrocarbon solvent can be obtained. That is, the hydrocarbon solvent is aggregated inside the particles, so that hollow portions containing the hydrocarbon solvent are formed inside the obtained precursor particles.

[0143] Furthermore, when a hydrophilic monomer (preferably an acid group-containing monomer) is used, the portion containing the hydrophilic monomer unit (preferably an acid group-containing monomer unit) in the shell portion swells in the base adding step described below, making it easy to remove the hydrocarbon solvent.

[0144] The type of hydrocarbon solvent is not particularly limited. Examples of the hydrocarbon solvent include relatively volatile solvents such as benzene, toluene, xylene, butane, pentane, hexane, cyclohexane, carbon disulfide, and carbon tetrachloride.

[0145] The hydrocarbon solvent used in the present invention preferably has a relative dielectric constant of 3 or less at 20°C. The relative dielectric constant is one of the indicators indicating the polarity of a compound. When the relative dielectric constant of the hydrocarbon solvent is sufficiently small, 3 or less, it is believed that phase separation in the monomer droplets proceeds rapidly and hollows are easily formed.

[0146] Examples of solvents having a relative dielectric constant of 3 or less at 20° C. are as follows. The values ​​in parentheses are relative dielectric constants.

[0147] Heptane (1.9), cyclohexane (2.0), benzene (2.3), toluene (2.4).

[0148] Regarding the relative dielectric constant at 20° C., the values ​​described in known literature (e.g., "Basic Handbook of Chemistry" compiled by the Chemical Society of Japan, revised in the 4th edition, Maruzen Co., Ltd., published on September 30, 1993, pages II-498 to II-503) and other technical information can be referred to. As a method for measuring the relative dielectric constant at 20° C., for example, a relative dielectric constant test performed in accordance with 23 of JIS C2101:1999 with a measuring temperature of 20° C. can be cited.

[0149] The hydrocarbon solvent used in the present invention may be a hydrocarbon compound having 5 to 7 carbon atoms. The hydrocarbon compound having 5 to 7 carbon atoms is easily enclosed in the precursor particles during the polymerization step, and can be easily removed from the precursor particles during the solvent removal step. Among them, the hydrocarbon solvent is preferably a hydrocarbon compound having 6 carbon atoms.

[0150] When the total mass of the (A) monomer and the (B) crosslinkable monomer is 100 parts by mass, the content of the (D) hydrocarbon solvent is preferably 100 to 900 parts by mass, more preferably 150 to 700 parts by mass, and further preferably 200 to 500 parts by mass. When the content of the (D) hydrocarbon solvent is 100 to 900 parts by mass, the porosity of the hollow resin particles in the obtained latex can be made higher than that of the prior art, and the mechanical properties of the hollow resin particles can be improved while maintaining the hollowness.

[0151] (F) Suspension stabilizer

[0152] The suspension stabilizer is an agent for stabilizing the suspension state in the suspension liquid in the suspension polymerization method described later.

[0153] The suspension stabilizer may contain a surfactant. The surfactant is a material that forms micelles in the suspension polymerization method described below, and the micelles contain at least one monomer selected from monovinyl monomers and hydrophilic monomers, a crosslinking monomer, an oil-soluble polymerization initiator, fats and oils, and a hydrocarbon solvent.

[0154] As the surfactant, a cationic surfactant, an anionic surfactant, and a nonionic surfactant can be used, and they can also be used in combination. Among them, anionic surfactants and nonionic surfactants are preferred, and anionic surfactants are more preferred.

[0155] Examples of the anionic surfactant include sodium dodecylbenzenesulfonate, sodium dodecyl sulfate, sodium dialkylsulfosuccinate, and formaldehyde condensate salts of naphthalenesulfonic acid.

[0156] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters.

[0157] Examples of the cationic surfactant include dodecyldimethylammonium chloride and octadecyltrimethylammonium chloride.

[0158] The suspension stabilizer may contain inorganic compounds that are poorly soluble in water, water-soluble polymers, and the like.

[0159] When the total mass of (A) monomer, (B) crosslinking monomer, (C) oil-soluble polymerization initiator and (E) hydrocarbon solvent is taken as 100 parts by mass, the content of (F) suspension stabilizer is preferably 0.1 to 3 parts by mass, more preferably 0.2 to 2 parts by mass, and further preferably 0.3 to 1 part by mass. When the above content of (F) suspension stabilizer is 0.1 parts by mass or more, micelles are easily formed in the aqueous medium. On the other hand, when the above content of (F) suspension stabilizer is 3 parts by mass or less, it is not easy to increase foaming and reduce productivity in the process of removing the hydrocarbon solvent.

[0160] (G) Water-based media

[0161] In the present invention, the aqueous medium refers to a medium selected from water, a hydrophilic solvent, and a mixture of water and a hydrophilic solvent.

[0162] The hydrophilic solvent in the present invention is not particularly limited as long as it is a solvent that can be fully mixed with water and does not cause phase separation. Examples of the hydrophilic solvent include alcohols such as methanol and ethanol; tetrahydrofuran (THF); and dimethyl sulfoxide (DMSO).

[0163] Among aqueous media, water is preferably used due to its high polarity. When a mixture of water and a hydrophilic solvent is used, it is important that the polarity of the mixture as a whole is not too low from the viewpoint of forming monomer droplets. In this case, for example, the mixing ratio (mass ratio) of water and the hydrophilic solvent can be water: hydrophilic solvent = 99:1 to 50:50.

[0164] (H) Others

[0165] The mixed solution prepared in this step is a composition in which the above-mentioned materials (A) to (G) are simply mixed and stirred appropriately. In the mixed solution, the oil phase containing the above-mentioned materials (A) to (E) is dispersed in the aqueous medium in a particle size of about several mm. The dispersion state of these materials in the mixed solution can be observed even with the naked eye depending on the type of the materials.

[0166] The mixed liquid preparation step may be a step of mixing an oil phase containing (A) monomers, (B) crosslinking monomers, (C) oil-soluble polymerization initiators, (D) fats and oils, and (E) hydrocarbon solvents with an aqueous phase containing (F) a suspension stabilizer and (G) an aqueous medium. By preparing the oil phase and the aqueous phase separately in advance and then mixing them, hollow resin particles having a uniform composition of the shell portion can be produced.

[0167] (2) Suspension preparation process

[0168] This step is a step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the above-mentioned mixed liquid.

[0169] In the suspension prepared in this step, monomer droplets containing the above materials (A) to (E) and having a particle size of about 0.1 μm to 9.0 μm are uniformly dispersed in the aqueous medium. Such monomer droplets are difficult to observe with the naked eye, but can be observed with a known observation device such as an optical microscope.

[0170] As described above, in the present invention, the suspension polymerization method is used instead of the emulsion polymerization method. Therefore, the advantages of using the suspension polymerization method and the oil-soluble polymerization initiator will be described below in comparison with the emulsion polymerization method.

[0171] Figure 5 Schematic diagram showing a dispersion liquid for emulsion polymerization. Figure 5 The micelle 60 in FIG. 1 schematically shows its cross section.

[0172] exist Figure 56 shows a micelle 60, a micelle precursor 60a, a monomer 53a dissolved in a solvent, and a water-soluble polymerization initiator 54 dispersed in an aqueous medium 51. The micelle 60 is formed by surrounding an oil-soluble monomer composition 53 with a surfactant 52. The monomer composition 53 contains monomers as raw materials of a polymer, etc., but does not contain a polymerization initiator.

[0173] On the other hand, the micelle precursor 60a is an aggregate of the surfactant 52, but does not contain a sufficient amount of the monomer composition 53. The micelle precursor 60a grows into a micelle 60 by absorbing the monomer 53a dissolved in the solvent into the interior or by taking part of the monomer composition 53 from other micelles 60 and the like.

[0174] The water-soluble polymerization initiator 54 diffuses in the aqueous medium 51 and penetrates into the micelle 60 and the micelle precursor 60a, promoting the growth of the oil droplets therein. Therefore, it can be predicted that in the emulsion polymerization method, although each micelle 60 is monodispersed in the aqueous medium 51, the particle size of the micelle 60 will grow to several hundred nanometers.

[0175] Figure 3 This is a schematic diagram showing one embodiment of the suspension in this process. Figure 3 The micelle 10 in the figure schematically shows its cross section. Figure 3 This is only a schematic diagram, and the suspension of the present invention is not limited to Figure 3 The content shown. Figure 3 A part of Figure 1 (2).

[0176] exist Figure 3 1 shows a case where micelles 10 and monomers 4a (including (A) monomers and (B) crosslinking monomers) dispersed in an aqueous medium are dispersed in an aqueous medium 1. The micelles 10 are formed by surrounding an oil-soluble monomer composition 4 with a surfactant 3. The monomer composition 4 contains an oil-soluble polymerization initiator 5, monomers (including (A) monomers and (B) crosslinking monomers), and a hydrocarbon solvent (all not shown).

[0177] like Figure 3 As shown, in this process, micro-oil droplets containing the monomer composition 4 are formed in advance inside the micelle 10, and then polymerization initiation radicals are generated in the micro-oil droplets by the oil-soluble polymerization initiator 5. Therefore, precursor particles of a target particle size can be produced without excessive growth of the micro-oil droplets.

[0178] In addition, suspension polymerization ( Figure 3 ) and emulsion polymerization ( Figure 5 ) by comparison, it can be seen that in suspension polymerization ( Figure 3), the oil-soluble polymerization initiator 5 has no chance to contact the monomer 4a dispersed in the aqueous medium 1. Therefore, by using an oil-soluble polymerization initiator, the target latex particles having a hollow portion can be generated, and in addition, the generation of excess polymer particles can be prevented.

[0179] One embodiment of this process is shown below. In addition, the present invention is not limited to the following embodiment.

[0180] The mixed liquid containing the above materials (A) to (G) is suspended to form monomer droplets. The method for forming the monomer droplets is not particularly limited, and can be carried out using a device capable of strong stirring, such as a (in-line) emulsifier disperser (manufactured by Pacifico Machinery Co., Ltd., trade name: Milder) or a high-speed emulsifier disperser (manufactured by PRIMIX CO., LTD., trade name: TKHOMOMIXER MARK II).

[0181] As described above, in this step, since phase separation occurs in the monomer droplets, the hydrocarbon solvent with low polarity tends to gather inside the monomer droplets. As a result, in the obtained droplets, the hydrocarbon solvent is distributed inside the droplets, and the materials other than the hydrocarbon solvent are distributed around the droplets.

[0182] (3) Polymerization process

[0183] This step is a step of subjecting the above suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion and containing a hydrocarbon solvent. Here, the precursor particles refer to particles mainly formed by copolymerization of the above (A) monomer and (B) crosslinkable monomer.

[0184] The polymerization method is not particularly limited, and may be, for example, batch, semi-continuous, or continuous. The polymerization temperature is preferably 40 to 80° C., more preferably 50 to 70° C. The polymerization reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours.

[0185] Since the monomer droplets containing the hydrocarbon solvent inside are used, the hollow space containing the hydrocarbon solvent is formed inside the precursor particles as described above.

[0186] (4) Alkali Addition Process

[0187] This step is performed only in the first manufacturing method.

[0188] This step is a step of adding a base to the precursor composition to adjust the pH of the precursor composition to 6.0 or higher. The addition of the base serves as an opportunity to remove the hydrocarbon solvent occupying the hollow part of the precursor particles.

[0189] In the first manufacturing method of the present invention, the base has at least two functions. The first function is to swell the part of the shell containing hydrophilic monomer units (preferably acid-containing monomer units) by reacting the base with the shell of the precursor particles. The second function is to saponify (hydrolyze) the fats and oils in the shell of the precursor particles by reacting the base with the fats and oils to form shell defects. These functions are opportunities to remove the hydrocarbon solvent occupying the hollow part of the precursor particles contained in the precursor composition, promote the formation of the hollow part inside the precursor, and expand the hollow part.

[0190] The base used in this step includes both a proton accepting compound (Brönsted base) and an electron pair donating compound (Lewis base).

[0191] The base is not particularly limited, and examples thereof include: alkali metal hydroxides such as sodium hydroxide, potassium hydroxide, and lithium hydroxide; alkaline earth metal hydroxides such as calcium hydroxide and magnesium hydroxide; ammonia; amine compounds such as dimethylamine and diethanolamine; alkali metal carbonates (hydrogen) salts such as sodium carbonate and potassium hydrogen carbonate; ammonium carbonates (hydrogen) salts such as ammonium hydrogen carbonate, etc. Among them, alkali metal hydroxides are particularly preferred.

[0192] The pH of the precursor composition after adding the base in this step is usually 6.0 or higher, preferably 6.5 or higher, more preferably 7.0 or higher, further preferably 7.5 or higher, and further preferably 8.0 or higher.

[0193] When the pH of the precursor composition is 6.0 or higher, the fats and oils in the precursor particles can be sufficiently saponified (hydrolyzed), and alkali swelling can be sufficiently performed.

[0194] The amount of the base added is preferably an amount that neutralizes at least a part of the acid groups in the shell portion of the precursor particles and thereby makes the pH of the obtained precursor composition 6.0 or higher.

[0195] In order to add a base to the precursor composition and swell the part of the shell of the precursor particles containing hydrophilic monomer units (preferably acid-containing monomer units), the base needs to be fully diffused in the precursor composition. Therefore, it is desirable to stir fully after adding the base. The processing time after adding the base is usually about 15 minutes to 60 minutes. Sometimes the stability of the precursor composition is reduced due to the addition of the base. In order to prevent this, an anionic surfactant or a nonionic surfactant can be added to the precursor composition alone or together before adding the base.

[0196] By carrying out the subsequent solvent removal step, a latex can be obtained. Unless an acid or base is further added, the pH of the latex is the same as the pH of the precursor composition in this step. Therefore, the pH of the obtained latex is preferably 6.0 or more, more preferably 6.5 or more, further preferably 7.0 or more, further preferably 7.5 or more, and particularly preferably 8.0 or more.

[0197] (5) Solvent Removal Process

[0198] This step is a step of removing the hydrocarbon solvent contained in the precursor particles in the precursor composition. By carrying out this step, a latex containing latex particles having a hollow portion can be obtained.

[0199] When removing the hydrocarbon solvent, the hydrocarbon solvent can be replaced by gas or other liquid (for example, an aqueous medium in which latex particles are suspended). By appropriately selecting the gas or other liquid, the environment inside the obtained latex particles can be changed, or hollow resin particles can be manufactured from the latex particles.

[0200] When the above hydrocarbon solvent is used, the obtained precursor composition can be easily removed from the hollow part of the precursor particles by, for example, decompression treatment, distillation treatment, stripping treatment, gas bubbling treatment, or a combination of two or more of these treatments. In addition, the hydrocarbon solvent occupying the hollow part can be easily replaced with water or an aqueous medium, and a latex containing latex particles in which the hollow part is occupied by water or an aqueous medium can be obtained.

[0201] (6) Others

[0202] As a process other than the above (1) to (5), for example, a process of appropriately drying a precursor composition or a latex can be mentioned, wherein the precursor composition includes precursor particles containing a hydrocarbon solvent, and the latex includes latex particles obtained by replacing the hydrocarbon solvent contained in the precursor particles with water or an aqueous medium. Through this process, the interior of the precursor particles can be replaced by a gas (e.g., air, an inert gas, etc.), and as a result, hollow resin particles can be produced. In the drying process, it is preferred to use a precursor composition containing precursor particles or a latex containing latex particles.

[0203] (7) Latex

[0204] The properties of the latex obtained in the above manner are not particularly limited. The latex can be used to form a heat-insulating layer of thermal paper, for example.

[0205] The number average particle size of the latex particles contained in the obtained latex is preferably 0.1 to 10 μm, more preferably 0.5 to 8 μm, further preferably 1 to 6 μm, further preferably 1.5 to 5 μm, and particularly preferably 2 to 4 μm. The number average particle size can be determined by measuring the particle sizes of 1,000 to 10,000 latex particles contained in the latex using, for example, a flow-type particle image analyzer and calculating the number average value thereof.

[0206] The porosity of the latex particles contained in the obtained latex is preferably 70% or more, more preferably 72% or more, further preferably 74% or more, further preferably 78% or more, particularly preferably 80% or more, and more particularly preferably 82% or more. From the viewpoint of maintaining the particle strength, the porosity of the latex particles may be 99% or less, or 95% or less. The porosity can be determined by measuring the maximum particle size and the maximum diameter of the voids for 200 latex particles contained in the latex using a transmission electron microscope, and simply averaging the porosities obtained based on the measurement results.

[0207] By drying the latex, hollow resin particles can be obtained.

[0208] (8) Hollow resin particles

[0209] The properties of the hollow resin particles are not particularly limited. The physical properties of the hollow resin particles include number average particle size, shape, and porosity. The evaluation items of the hollow resin particles include the amount of volatile organic compounds contained in the hollow resin particles and the heat resistance of the hollow resin particles.

[0210] a. Number average particle size of hollow resin particles

[0211] The number average particle size of the hollow resin particles is preferably 0.1 to 10 μm, more preferably 0.5 to 8 μm, further preferably 1 to 6 μm, further preferably 1.5 to 5 μm, and particularly preferably 2 to 4 μm.

[0212] The number average particle size of the hollow resin particles can be determined by measuring the particle size distribution using, for example, a laser diffraction particle size distribution measuring apparatus and calculating the number average value thereof.

[0213] The coefficient of variation of the number average particle size of the hollow resin particles can be determined by measuring the number-based particle size distribution using, for example, a laser diffraction particle size distribution measuring apparatus and dividing the standard deviation by the number average particle size.

[0214] In the first manufacturing method of the present invention, the hollow part is formed without expanding the shell part, so that hollow resin particles with a small coefficient of variation of the number average particle size (i.e., hollow resin particles with a narrow particle size distribution) can be obtained. In addition, the narrower the particle size distribution of the hollow resin particles, the more flat the coating film containing the hollow resin particles can be formed.

[0215] b. Shape of hollow resin particles

[0216] The shape of the hollow resin particles is not particularly limited as long as a hollow portion is formed inside, and examples thereof include spherical, ellipsoidal, and irregular shapes, etc. Among these, a spherical shape is particularly preferred from the perspective of ease of production.

[0217] The particle may have one or more hollow parts inside, or may be porous. In order to maintain a good balance between the high porosity of the hollow resin particle and the mechanical strength of the hollow resin particle, the particle preferably has only one hollow part inside.

[0218] The average circularity of the hollow resin particles may be 0.950 to 0.995.

[0219] An example of the shape of the hollow resin particles is a bag formed of a thin membrane and inflated by being filled with gas. The cross-sectional view thereof is as described below. Figure 2 In this example, a thin film is provided on the outside, and the inside is filled with gas.

[0220] The particle shape can be confirmed by, for example, SEM or TEM. In addition, the shape of the interior of the particle can be confirmed by SEM or TEM after the particle is cross-sectioned using a known method.

[0221] c. Porosity of hollow resin particles

[0222] The porosity of the hollow resin particles is preferably 70% or more, more preferably 72% or more, further preferably 74% or more, further preferably 78% or more, particularly preferably 80% or more, and further preferably 82% or more. From the viewpoint of maintaining the particle strength, the porosity of the hollow resin particles may be 99% or less, or 95% or less.

[0223] The void ratio (%) of the hollow resin particles can be calculated by the following formula (I) from the apparent density D1 and the true density D0 of the hollow resin particles.

[0224] Formula (I)

[0225] Void ratio (%) = 100 - (apparent density D1 / true density D0) × 100

[0226] The method for measuring the apparent density D1 of the hollow resin particles is as follows. First, 3 Fill the volumetric flask to about 30 cm 3 The mass of the hollow resin particles filled with the hollow resin particles is accurately weighed. Next, the volumetric flask filled with the hollow resin particles is accurately filled with isopropyl alcohol up to the standard line, taking care not to introduce bubbles. The mass of the isopropyl alcohol added to the volumetric flask is accurately weighed, and the apparent density D1 (g / cm 3 ).

[0227] Formula (II)

[0228] Apparent density D1 = [mass of hollow resin particles] / (100 - [mass of isopropyl alcohol] ÷ [specific gravity of isopropyl alcohol at the measurement temperature])

[0229] The apparent density D1 corresponds to the specific gravity of the entire hollow resin particle when the hollow portion is regarded as a part of the hollow resin particle.

[0230] The method for measuring the true density D0 of the hollow resin particles is as follows. The hollow resin particles are crushed in advance and then placed in a container with a capacity of 100 cm 3 A volumetric flask is filled with about 10 g of crushed pieces of hollow resin particles, and the mass of the crushed pieces filled is accurately weighed. Then, isopropyl alcohol is added to the volumetric flask in the same manner as the above-mentioned apparent density measurement, and the mass of isopropyl alcohol is accurately weighed. The true density D0 (g / cm2) of the hollow resin particles is calculated based on the following formula (III): 3 ).

[0231] Formula (III)

[0232] True density D0 = [mass of crushed pieces of hollow resin particles] / (100 - [mass of isopropyl alcohol] ÷ [specific gravity of isopropyl alcohol at the measurement temperature])

[0233] The true density D0 corresponds to the specific gravity of only the shell portion of the hollow resin particle. As is clear from the above-mentioned measurement method, when calculating the true density D0, the hollow portion is not considered as a part of the hollow resin particle.

[0234] The porosity of the hollow resin particles can also be expressed in another way, that is, the proportion of the hollow part in the specific gravity of the hollow resin particles.

[0235] d. Volatile organic compounds contained in hollow resin particles

[0236] The amount of volatile organic compounds contained in the hollow resin particles of the present invention is usually 5 mass % or less, preferably 4 mass % or less, more preferably 3 mass % or less, further preferably 2 mass % or less, further preferably 1 mass % or less, and particularly preferably less than 1 mass %.

[0237] In the present invention, "volatile organic compounds contained in hollow resin particles" refers to organic compounds having a boiling point of 400° C. or less among the organic compounds contained in the hollow resin particles. Typical examples of volatile organic compounds include hydrocarbon solvents and unreacted monomers used in the production method described below, but are not limited to these typical examples.

[0238] The method for determining the amount of volatile organic compounds contained in hollow resin particles is as follows. Add about 100 mg of hollow resin particles to a 30 mL screw-cap glass bottle and weigh accurately. Next, add about 10 g of tetrahydrofuran (THF) and weigh accurately. Stir the mixture in the glass bottle with a stirrer for 1 hour to extract the volatile organic compounds contained in the hollow resin particles. Stop stirring, allow the resin components of the hollow resin particles that are insoluble in THF to precipitate, then attach a filter (made by Advantech Co., Ltd., trade name: Membrane Filter 25JP020AN) to a syringe, filter the precipitate to obtain a sample solution, inject the sample solution into a gas chromatograph (GC) for analysis. The amount of volatile organic compounds per unit mass of the hollow resin particles (mass %) is calculated based on the peak area of ​​GC and a pre-made standard curve. The specific analysis conditions are as follows.

[0239] (Analysis conditions)

[0240] Apparatus: GC-2010 (manufactured by Shimadzu Corporation)

[0241] Column: DB-5 (manufactured by Agilent Technologies Inc.)

[0242] df=0.25μm 0.25mm ID×30m

[0243] Detector: FID

[0244] Carrier gas: nitrogen (linear velocity: 28.8 cm / sec)

[0245] Inlet temperature: 200℃

[0246] Detector temperature: 250°C

[0247] Oven temperature: increase from 40°C to 230°C at a rate of 10°C / min, and maintain at 230°C for 2 minutes.

[0248] Sample volume: 2 μL

[0249] e. Heat resistance of hollow resin particles

[0250] The hollow resin particles of the present invention are unlikely to collapse in external and internal shapes even under high temperature conditions, and thus can maintain their hollowness.

[0251] As an index of heat resistance, for example, the density change rate d before and after the heat treatment of the hollow resin particles can be considered.

[0252] The density change rate d is calculated as follows: First, the hollow resin particles are allowed to stand for 10 minutes in an electric furnace set at 200° C. to perform a heat treatment. Next, the hollow resin particles are taken out of the electric furnace, and the apparent density of the hollow resin particles is measured in the same manner as the method for measuring the apparent density D1.

[0253] The apparent density of the hollow resin particles after heat treatment is defined as D a The apparent density of the hollow resin particles before heat treatment is set as D b (= the above-mentioned apparent density D1), the density change rate d (%) was calculated based on the following formula (IV).

[0254] Formula (IV)

[0255] d={|D a -D b | / D b}×100

[0256] The smaller the density change rate d is, the smaller the influence of the heat treatment on the hollow resin particles is, that is, the higher the heat resistance of the hollow resin particles is.

[0257] 6. Application of hollow resin particles

[0258] As the use of hollow resin particles, for example, the base coating material of thermal paper can be considered. Generally, the base coating material requires heat insulation and cushioning properties, and in addition, heat resistance suitable for thermal paper use is also required. The hollow resin particles of the present invention can meet these requirements due to their high porosity, indestructible hollow shape, small number average particle size and high heat resistance.

[0259] In addition, the hollow resin particles can also be used for plastic pigments with excellent gloss, hiding power, etc. In addition, useful components such as fragrances, medicines, pesticides, ink components, etc. are enclosed in the interior of the hollow resin particles by means of impregnation treatment, reduced pressure or pressurized impregnation treatment, etc., to obtain hollow resin particles, and such hollow resin particles can be used for various purposes depending on the components contained inside.

[0260] 2. Second Manufacturing Method

[0261] The production method of the present invention comprises (1) a mixed solution preparation step, (2) a suspension preparation step, (3) a polymerization step, (4) a solid-liquid separation step, and (5) a solvent removal step. The production method of the present invention is not limited to these five steps.

[0262] Figure 2 This is a schematic diagram showing an example of the second production method of the present invention. Figure 2 (1) to (5) in the figure correspond to the above-mentioned steps (1) to (5). The white arrows between the figures indicate the order of the steps.

[0263] Figure 2 (1) and (2) correspond to Figure 1 (1) or (2). In addition, Figure 2 (3) corresponds to the case 6 except that the case 6 does not contain grease 13. Figure 1 (3).

[0264] Figure 2 (4) is a schematic cross-sectional view showing one embodiment of the precursor particles after the solid-liquid separation step. Figure 2 (4) shows that from the above Figure 2 The state of separating the aqueous medium 1 in the state (3).

[0265] Figure 2 (5) is a schematic cross-sectional view showing one embodiment of the hollow resin particles after the solvent removal step. Figure 2 (5) shows that from the above Figure 2 The state in which the hydrocarbon solvent 7 is removed from the state (4) is obtained. As a result, a hollow resin particle 100C having a hollow portion 8 inside the shell portion 6 is obtained.

[0266] Hereinafter, the above-mentioned five steps and other steps will be described in order, centering on the differences from the first manufacturing method.

[0267] (1) Mixed solution preparation process

[0268] This step is a step of preparing a mixed solution, which contains (A) at least one monomer selected from a monovinyl monomer and a hydrophilic monomer (but excluding acrylonitrile and methacrylonitrile), (B) a crosslinking monomer, (C) an oil-soluble polymerization initiator, (E) a hydrocarbon solvent, (F) a suspension stabilizer, and (G) an aqueous medium.

[0269] In the second production method, it is not necessary to use (D) fats and oils as in the above-mentioned first production method. In the second production method, it is preferred that the mixed liquid does not contain fats and oils.

[0270] In the second production method, neither acrylonitrile nor methacrylonitrile is used as a hydrophilic monomer. This is because, as shown in Comparative Example II-5 described later, these monomers containing a heat-labile nitrile group have poor heat resistance, resulting in a low porosity of the obtained particles.

[0271] In the mixed solution used in the second manufacturing method, when the total mass of the (A) monomer and the (B) crosslinkable monomer is 100 parts by mass, the content of the (B) crosslinkable monomer is usually 25 to 59 parts by mass, preferably 28 to 58 parts by mass, more preferably 30 to 57 parts by mass, and further preferably 35 to 55 parts by mass. If the content of the (B) crosslinkable monomer is 25 to 59 parts by mass, the risk of collapse of the obtained hollow resin particles is low, so the porosity of the hollow resin particles can be maintained high, and the risk of a large amount of hydrocarbon solvent remaining in the hollow resin particles is also low.

[0272] In addition, the mixed liquid may contain other polymerizable monomers in addition to the (A) monomer and the (B) crosslinkable monomer.

[0273] The mixed solution preparation step may be a step of mixing the following oil phase and the following water phase, wherein the above oil phase contains at least one monomer selected from the monovinyl monomer and the hydrophilic monomer, a cross-linking monomer, an oil-soluble polymerization initiator, and a hydrocarbon solvent, and when the total mass of the above at least one monomer selected from the monovinyl monomer and the hydrophilic monomer and the cross-linking monomer is taken as 100 parts by mass, the content of the cross-linking monomer is 25 to 59 parts by mass, and the above water phase contains the above suspension stabilizer and an aqueous medium. By preparing the oil phase and the water phase separately in advance and then mixing them, hollow resin particles having a uniform composition of the shell portion can be manufactured.

[0274] (2) Suspension preparation step and (3) Polymerization step

[0275] These two steps in the second production method are not particularly different from those in the first production method.

[0276] (4) Solid-liquid separation process

[0277] This step is a step of obtaining precursor particles by subjecting the above-mentioned precursor composition to solid-liquid separation.

[0278] As shown in Comparative Example II-3 described later, when the hydrocarbon solvent contained in the precursor particles is removed from the slurry containing the aqueous medium, there is a problem that the obtained hollow resin particles will be damaged if water equal to the volume of the hydrocarbon solvent removed from the precursor particles does not enter the particles.

[0279] As one method for preventing this problem, as described above, it is conceivable to adjust the pH of the slurry constituting the precursor composition to 6.0 or more, then swell the shell of the precursor particles with alkali, and then remove the hydrocarbon solvent (refer to the first production method described above). In this case, the shell of the precursor particles acquires flexibility, so that the hydrocarbon solvent and water inside the precursor particles can be quickly replaced, and precursor particles containing water can be obtained.

[0280] In contrast, in the second manufacturing method, after the slurry after the polymerization step is subjected to solid-liquid separation, the obtained solid component is dried in the gas phase. In this case, air equal to the volume of the hydrocarbon solvent removed from the inside of the precursor particles is easy to enter the particles, so that hollow resin particles with a hollow shape can be obtained. Moreover, the precursor particles containing the hydrocarbon solvent have a tendency to be less susceptible to damage than the precursor particles containing water.

[0281] The reason why the precursor particles containing a hydrocarbon solvent are less susceptible to damage than the precursor particles containing water is not clear, but the following principle can be inferred when the free volume of the polymer constituting the shell is taken into consideration.

[0282] In the model proposed by H. Eyring to explain the structure of liquids, liquids are composed of molecules and free volume (i.e., space without molecules). The free volume is formed by a collection of molecular-sized pores in the liquid, and at normal temperature and pressure, the free volume accounts for about 3% of the liquid. This model can also be applied to solid structures containing regular molecules such as polymers.

[0283] In the present invention, the polarity of the polymer constituting the shell of the precursor particles is usually high. Therefore, it can be considered that water is easily affinity to the polymer, and water molecules are easy to penetrate into the free volume of the polymer. In other words, the solubility coefficient of water molecules in the polymer is high. On the other hand, hydrocarbon solvents are not easy to be affinity to the polymer due to their low polarity. In other words, the solubility coefficient of hydrocarbon solvent molecules in the polymer is low. As a result, hydrocarbon solvent molecules are not easy to penetrate into the free volume of the polymer.

[0284] Therefore, in the particles containing water, water molecules penetrate into the free volume of the polymer constituting the shell, so that the space in the shell where no molecules exist is reduced, and as a result, the air permeability in the shell is reduced, and the air inflow accompanying the evaporation of water during drying is difficult to proceed, and the particles are easily damaged. In contrast, in the particles containing a hydrocarbon solvent, the hydrocarbon solvent molecules are difficult to penetrate into the free volume of the polymer, and therefore the air permeability in the shell is maintained high. As a result, in the solvent removal step, the replacement of the hydrocarbon solvent with air proceeds rapidly, and hollow resin particles with a hollow portion maintained are generated.

[0285] The method for solid-liquid separation of the precursor composition is not particularly limited as long as it is a method for separating the solid component comprising the precursor particles and the liquid component comprising the aqueous medium without removing the hydrocarbon solvent contained in the precursor particles, and a known method can be used. As the method for solid-liquid separation, for example, centrifugation, filtration, static separation, etc. can be cited, especially, centrifugation or filtration can be used, and from the viewpoint of ease of operation, centrifugation can be used.

[0286] After the solid-liquid separation step and before the solvent removal step described below, an arbitrary step such as a pre-drying step may be performed. As the pre-drying step, for example, a step of pre-drying the solid component obtained after the solid-liquid separation step using a drying device such as a dryer or a drying tool such as a hand dryer may be mentioned.

[0287] (5) Solvent Removal Process

[0288] This step is a step of obtaining hollow resin particles by removing the hydrocarbon solvent contained in the precursor particles in a gas phase.

[0289] Strictly speaking, "in the gas phase" in this process refers to an environment in which there is no liquid component outside the precursor particles, and an environment in which there is only a very small amount of liquid component outside the precursor particles that does not affect the removal of the hydrocarbon solvent. "In the gas phase" can also be said to be a state in which the precursor particles are not present in the slurry, or a state in which the precursor particles are present in the dry powder. That is, in this process, it is very important to remove the hydrocarbon solvent in an environment in which the precursor particles are in direct contact with the external gas.

[0290] As shown in Examples II-1 to II-4 described later, the fact that the hollow resin particles maintain a spherical shape after vacuum drying and restoration to normal pressure in the solvent removal step is considered to be evidence of high air permeability of the shell itself.

[0291] Generally, it is known that nylon, ethylene vinyl alcohol (EVOH), etc. have improved air permeability under high humidity. The reason is understood to be that these polymers are plasticized due to water molecules, and as a result, the mobility of the polymer becomes higher. However, the hollow resin particles of the present invention, especially the hollow resin particles obtained by the second manufacturing method, are considered to have a high degree of crosslinking, so it is speculated that the influence of plasticization caused by the action of the aqueous medium is small. Therefore, in the present invention, the air permeability of the shell portion of the hollow resin particles can be considered to be a property inherent to the polymer constituting the shell portion.

[0292] The method for removing the hydrocarbon solvent in the precursor particles in the gas phase is not particularly limited, and a known method can be adopted, such as reduced pressure drying, heating drying, air flow drying, or a combination of these methods.

[0293] In particular, when the heating drying method is used, the heating temperature needs to be above the boiling point of the hydrocarbon solvent and below the highest temperature at which the shell structure of the precursor particles is not damaged. Therefore, the heating temperature is determined according to the composition of the shell in the precursor particles and the type of the hydrocarbon solvent. For example, the heating temperature can be 50 to 200°C, 70 to 180°C, or 100 to 150°C.

[0294] By the drying operation in the gas phase, the hydrocarbon solvent inside the precursor particles is replaced by the external gas, and as a result, hollow resin particles having a hollow portion occupied by the gas can be obtained.

[0295] The drying atmosphere is not particularly limited and can be appropriately selected according to the purpose of the hollow resin particles. Examples of the drying atmosphere include air, oxygen, nitrogen, argon, etc. In addition, after the inside of the hollow resin particles is temporarily filled with gas, it is also possible to obtain hollow resin particles whose inside is temporarily vacuum by performing reduced pressure drying.

[0296] (6) Others

[0297] As a process other than the above (1) to (5), for example, a process of replacing the gas inside the hollow resin particle with another gas or liquid can be mentioned. By such replacement, the environment inside the hollow resin particle can be changed, molecules can be selectively enclosed inside the hollow resin particle, or the chemical structure inside the hollow resin particle can be modified according to the application.

[0298] The description about the first manufacturing method mentioned above can be applied to the second manufacturing method as long as there is no obstacle. In addition, the description about the second manufacturing method mentioned above can also be applied to the first manufacturing method as long as there is no obstacle.

[0299] Example

[0300] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts and % are based on mass unless otherwise specified.

[0301] The test methods performed in the present examples and comparative examples are as follows.

[0302] <Example Series I>

[0303] I-1. Production of Latex Containing Hollow Resin Particles

[0304] [Example I-1]

[0305] (1) Mixed solution preparation process

[0306] The following materials were added to a pressure-resistant container equipped with a stirring device into which 325 parts of ion-exchanged water as an aqueous medium had been added, and the contents in the container were stirred to disperse the following materials in the ion-exchanged water to prepare a mixed solution.

[0307] 0.3 parts of anionic surfactant

[0308] ·Butyl acrylate (BA) 6 parts

[0309] ·Methyl methacrylate (MMA) 15 parts

[0310] ·Methacrylic acid (MAA, hydrophilic monomer (acid group-containing monomer)) 9 parts

[0311] ·100 parts of cyclohexane

[0312] ·3 parts linseed oil

[0313] ·Divinylbenzene 2 parts

[0314] 2,2'-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator, manufactured by Wako Pure Chemical Corporation, trade name: V-65) 0.63 parts

[0315] (2) Suspension preparation process

[0316] The mixed liquid was stirred and suspended by an emulsifying disperser to prepare a suspension in which monomer droplets containing cyclohexane were dispersed in water.

[0317] (3) Polymerization process

[0318] The suspension was added to a reaction vessel to which 0.6 parts of anionic surfactant had been added, and the temperature was raised to 65°C, and then maintained at 65°C for 3 hours to perform a polymerization reaction. Through the polymerization reaction, a precursor composition containing precursor particles containing cyclohexane was prepared. Then, the reaction vessel was cooled to room temperature.

[0319] (4) Alkali Addition Process

[0320] A 10% by mass sodium hydroxide aqueous solution was added to the cooled precursor composition in the reaction container until the pH of the mixture in the reaction container reached 7.0. The sodium hydroxide aqueous solution was added while stirring the precursor composition using the inline emulsifier.

[0321] (5) Solvent Removal Process

[0322] A defoamer in the range of 0.1 to 0.5 parts by mass was further added to 100 parts by mass of the precursor composition after the above-mentioned alkali addition step, and nitrogen was blown in at a flow rate of 6 minutes / L while maintaining at 70°C for 6 hours to remove cyclohexane from the precursor particles, thereby obtaining a latex (Example I-1). According to the observation results of a transmission electron microscope, the latex was a latex containing latex particles having a hollow portion (the same below).

[0323] [Example I-2]

[0324] A latex was obtained by the same production method as in Example I-1 except that the pH was changed from 7.0 to 7.5 in the "(4) alkali adding step" of Example I-1 (Example I-2).

[0325] [Example I-3]

[0326] A latex was obtained by the same production method as in Example I-1 except that the pH was changed from 7.0 to 8.5 in the "(4) alkali adding step" of Example I-1 (Example I-3).

[0327] [Comparative Example I-1]

[0328] A latex was obtained by the same production method as in Example I-1 except that the "(4) alkali addition step" of Example I-1 was not carried out (Comparative Example I-1). In addition, the particles contained in this latex were not latex particles having a hollow portion.

[0329] [Comparative Example I-2]

[0330] A latex was obtained by the same production method as in Example I-1 except that the pH was changed from 7.0 to 5.0 in the "(4) alkali addition step" of Example I-1 (Comparative Example I-2). The particles contained in the latex were not latex particles having a hollow portion.

[0331] [Comparative Example I-3]

[0332] A latex (Comparative Example I-3) was obtained by the same production method as in Example I-1 except that divinylbenzene was not added in the "(1) Dispersion Preparation Step" of Example I-1. The particles contained in the latex were not latex particles having a hollow portion.

[0333] [Comparative Example I-4]

[0334] In the "(1) Dispersion Preparation Step" of Example I-1, except that acrylic acid (MAA, hydrophilic monomer (acid group-containing monomer)) was not added, a latex (Comparative Example I-4) was obtained by the same production method as Example I-1. In addition, the particles contained in the latex were not latex particles having a hollow portion.

[0335] [Comparative Example I-5]

[0336] A latex (Comparative Example I-5) was obtained by the same production method as in Example I-1 except that linseed oil was not added in the "(1) Dispersion Preparation Step" of Example I-1. The particles contained in the latex were not latex particles having a hollow portion.

[0337] I-2. Evaluation of latex

[0338] The porosity and number average particle size of latex particles contained in each of the latexes of Examples I-1 to I-3 and Comparative Examples I-1 to I-5 were measured. The details are as follows.

[0339] (1) Porosity of Latex Particles Having Hollow Parts

[0340] The maximum particle size and the maximum diameter of the hollow portion of 200 latex particles having a hollow portion contained in the latexes of Examples I-1 to I-3 were measured using a transmission electron microscope (trade name "H-7500", manufactured by Hitachi, Ltd.). The porosity of each latex particle was calculated using these two measured values ​​according to the following formula (A), and the simple average value thereof was taken as the porosity of the latex particles.

[0341] Formula (A)

[0342] Void ratio (%) = {(maximum diameter of hollow part) 3 / (Maximum particle size) 3}×100

[0343] In addition, since no hollow part was observed in the latex particles contained in the latexes of Comparative Examples I-1 to I-5, the void ratio was not calculated.

[0344] (2) Number average particle size of latex particles

[0345] During the measurement, the latex particle concentration in the latex is adjusted to 3000 to 10000 particles / μL, and then the particle size of 1000 to 10000 particles is measured using a flow cytometric particle image analyzer (trade name "FPIA-3000", manufactured by Sysmex Corporation), and the number average value is calculated. The obtained value is used as the number average particle size of the latex particles.

[0346] The measurement and evaluation results of each latex of Examples I-1 to I-3 and Comparative Examples I-1 to I-5 are shown in the following Table 1. In addition, as described above, since no hollow part was observed in the latex particles contained in the latexes of Comparative Examples I-1 to I-5, the porosity of these latex particles is not described in the following Table I-1.

[0347] [Table I-1]

[0348]

[0349] I-3. Examination Next, with reference to Table I-1, the evaluation results of latex were examined.

[0350] According to Table I-1, the number average particle size of the latex particles contained in the latex of Comparative Example I-1 is 4.1 μm and does not have a hollow portion. Therefore, it can be seen that if no alkali is added to the precursor composition, latex particles without a hollow portion are obtained. This is considered to be because, when no alkali is added, the portion containing the hydrophilic monomer unit in the shell of the precursor particles does not swell with alkali and dissolve out fats and oils.

[0351] According to Table I-1, the number average particle size of the latex particles contained in the latex of Comparative Example I-2 is 4.0 μm and has no hollow part. Therefore, it can be seen that even if an alkali is added to the precursor composition, if the pH of the precursor composition is not 6.0 or more, latex particles without a hollow part are obtained. It is believed that the reason is that when the pH of the precursor composition is not 6.0 or more, the alkali swelling of the part containing the hydrophilic monomer unit in the shell part of the precursor particle is insufficient.

[0352] According to Table I-1, the shell of the latex particles contained in the latex of Comparative Example I-3 was dissolved and agglomerated, so the number average particle size could not be measured and there was no hollow part. Therefore, it can be seen that when no cross-linking monomer is used, latex particles without a hollow part are obtained. It can be considered that the reason is that although the part containing the hydrophilic monomer unit in the shell of the precursor particles is alkali-swollen by adding an alkali, if there is no cross-linking monomer, the part is dissolved into the aqueous medium, and as a result, the hollow part cannot be maintained, and the precursor particles are damaged.

[0353] According to Table I-1, the number average particle size of the latex particles contained in the latex of Comparative Example I-4 was 4.4 μm and had no hollow part. Therefore, it can be seen that when no hydrophilic monomer is used, latex particles without hollow parts are obtained. This is considered to be because when no hydrophilic monomer is used, the obtained precursor particles do not swell due to alkali.

[0354] According to Table I-1, the number average particle size of the latex particles contained in the latex of Comparative Example I-5 is 4.3 μm and has no hollow part. Therefore, it can be seen that when no fat is used, latex particles without a hollow part are obtained. It is believed that the reason is that when no fat is used, the shell part of the precursor particles does not have defects, so the hydrocarbon solvent contained in the shell cannot be removed in the solvent removal step.

[0355] On the other hand, according to Table I-1, the number average particle size of the latex particles contained in the latexes of Examples I-1 to I-3 was 4.3 to 4.4 μm, and the porosity was 80% in all cases.

[0356] Therefore, it can be proved that by sequentially preparing a mixed solution, a suspension, and a precursor composition, adding an alkali to the obtained precursor composition, and removing the hydrocarbon solvent contained in the precursor particles, a latex containing latex particles with a higher porosity than the prior art can be efficiently produced. In addition, hollow resin particles can be obtained by subjecting the latex to a drying step.

[0357] <Example Series II>

[0358] II-1. Production of hollow resin particles

[0359] [Example II-1]

[0360] (1) Mixed solution preparation process

[0361] First, the following materials (a1) to (d1) are mixed, and the obtained mixture is used as an oil phase.

[0362] (a1) 41 parts of methacrylic acid

[0363] (b) 59 parts of ethylene glycol dimethacrylate

[0364] (c) 2,2'-azobis(2,4-dimethylvaleronitrile) (oil-soluble polymerization initiator, manufactured by Wako Pure Chemical Corporation, trade name: V-65) 3 parts

[0365] (e1) 300 parts of cyclohexane

[0366] Next, 3 parts of (f) surfactant were added to 800 parts of (g) ion exchange water, and the obtained mixture was used as an aqueous phase.

[0367] The aqueous phase and the oil phase are mixed to prepare a mixed solution.

[0368] (2) Suspension preparation process

[0369] The mixed liquid was stirred and suspended using an emulsifying disperser to prepare a suspension in which monomer droplets containing cyclohexane were dispersed in water.

[0370] (3) Polymerization process

[0371] The suspension was stirred for 4 hours under a nitrogen atmosphere at a temperature of 65° C. to perform a polymerization reaction. Through the polymerization reaction, a precursor composition containing precursor particles containing cyclohexane was prepared.

[0372] (4) Solid-liquid separation process

[0373] The obtained precursor composition was centrifuged using a cooling high-speed centrifuge (manufactured by Kokusan, Inc., trade name: H-9R) with rotor MN1, rotation speed 3000 rpm, and centrifugal separation time of 20 minutes to dehydrate the solid component. The dehydrated solid component was dried at 40° C. using a dryer to obtain precursor particles containing cyclohexane.

[0374] (5) Solvent Removal Process

[0375] The precursor particles were heated in a vacuum dryer at 150° C. for 15 hours in a gas phase to obtain resin particles of Example II-1. The results of observation with a scanning electron microscope and the porosity value confirmed that the resin particles were spherical and had only one hollow portion.

[0376] [Example II-2]

[0377] In the "(1) mixed solution preparation step" of Example II-1, the resin particles of Example II-2 were obtained by the same manufacturing method as Example II-1, except that the materials and addition amounts shown in Table II-1 were used. The results of observation under a scanning electron microscope and the value of the porosity confirmed that the resin particles were spherical and had only one hollow portion.

[0378] [Example II-3]

[0379] The resin particles of Example II-3 were obtained by the same manufacturing method as Example II-1, except that the materials and addition amounts shown in Table II-1 were used in the "(1) Mixed Liquid Preparation Step" of Example II-1, and filtration was used in the "(4) Solid-Liquid Separation Step". The results of observation with a scanning electron microscope and the value of the porosity confirmed that the resin particles were spherical and had only one hollow portion.

[0380] In addition, the solid-liquid separation step using filtration in Example II-3 is as follows. For the precursor composition obtained by the polymerization step, a pressure filter (Advantech Toyo Corporation, trade name: KST-90-UH) and a qualitative filter paper (Advantech Toyo Corporation, No. 2) were used to dehydrate the solid content under a pressure of 0.29 MPa. The dehydrated solid content was dried at a temperature of 40° C. using a dryer to obtain precursor particles containing cyclohexane.

[0381] [Example II-4]

[0382] In the "(1) mixed solution preparation step" of Example II-1, the resin particles of Example II-4 were obtained by the same manufacturing method as Example II-1, except that the materials and addition amounts shown in Table II-1 were used. The results of observation with a scanning electron microscope and the value of the porosity confirmed that the resin particles were spherical and had only one hollow portion.

[0383] [Comparative Example II-1]

[0384] In the "(1) mixed solution preparation step" of Example II-1, the resin particles of Comparative Example II-1 were obtained by the same manufacturing method as Example II-1, except that the materials and addition amounts shown in Table II-1 were used. In the resin particles, the amount of volatile organic compounds was 30% by mass, so it was confirmed that a large amount of hydrocarbon solvent remained in the resin particles. In addition, the true density of the resin particles could not be measured. According to the results of observation with a scanning electron microscope, it was confirmed that these resin particles were spherical.

[0385] [Comparative Example II-2]

[0386] In the "(1) mixed solution preparation step" of Example II-3, the resin particles of Comparative Example II-2 were obtained by the same manufacturing method as Example II-3, except that the materials and addition amounts shown in Table II-1 were used. According to the results of observation with a scanning electron microscope, it was confirmed that these resin particles were damaged and irregular in shape.

[0387] [Comparative Example II-3]

[0388] In the "(1) mixed solution preparation step" of Example II-1, the materials and addition amounts shown in Table II-1 were used. In addition, the same "(2) suspension preparation step" and "(3) polymerization step" as in Example II-1 were performed to prepare a precursor composition containing precursor particles containing cyclohexane. Thereafter, 0.3 parts of a defoaming agent was added to the precursor composition, nitrogen was blown in at a flow rate of 6 min / L, and the temperature was maintained at 90° C. for 15 hours to remove cyclohexane from the precursor particles.

[0389] The obtained precursor particles were heated at 40° C. for 24 hours in a normal pressure dryer to completely remove moisture, thereby obtaining resin particles of Comparative Example II-3. Observation with a scanning electron microscope revealed that these resin particles were damaged and irregular in shape.

[0390] [Comparative Example II-4]

[0391] In the "(1) mixed solution preparation step" of Example II-1, the resin particles of Comparative Example II-4 were obtained by the same manufacturing method as Example II-1, except that the materials and addition amounts shown in Table II-1 were used. In these resin particles, the amount of volatile organic compounds was 55% by mass, and it was confirmed that a large amount of hydrocarbon solvent remained in the resin particles. In addition, the true density of these resin particles could not be measured. According to the results of observation with a scanning electron microscope, these resin particles were confirmed to be spherical.

[0392] [Comparative Example II-5]

[0393] First, the following materials (a2), (α1), (α2), (c), and (e2) are mixed and the resulting mixture is used as an oil phase.

[0394] (a2) 5 parts of methyl methacrylate

[0395] (α1) 60 parts of acrylonitrile

[0396] (α2) 35 parts of methacrylonitrile

[0397] (c) 5 parts of azobisisobutyronitrile

[0398] (e2) 30 parts of isopentane

[0399] Next, 200 parts of (y) colloidal silica dispersion (average particle size 5 nm, colloidal silica effective concentration 20% by mass) were added to 600 parts of (g) ion exchange water, and the obtained mixture was used as an aqueous phase.

[0400] The aqueous phase and the oil phase are mixed to prepare a mixed solution.

[0401] The mixed solution was stirred at 4000 rpm for 1 minute using a disperser (manufactured by PRIMIX, trade name: HOMOMIXER) to suspend the mixture, and the obtained suspension was stirred at 60° C. for 10 hours to perform a polymerization reaction.

[0402] The suspension after the polymerization reaction was completed was filtered, and the obtained solid content was dried in a dryer at 40° C. to obtain heat-expandable microcapsules.

[0403] 100 parts of the obtained heat-expandable microcapsules were heat-treated at 180° C. for 3 minutes in a gas phase using a dryer to obtain resin particles (hollow resin particles) of Comparative Example II-5.

[0404] II-2. Measurement and evaluation of resin particles

[0405] The following measurements and evaluations were performed on each of the resin pellets of Examples II-1 to II-4 and Comparative Examples II-1 to II-5. The details are as follows.

[0406] (1) Determination of the number average particle size of resin particles and calculation of the coefficient of variation

[0407] The particle diameter of each resin particle was measured using a laser diffraction particle size distribution measuring device (manufactured by Shimadzu Corporation, trade name: SALD-2000), and the number average value thereof was calculated. The obtained value was defined as the number average particle diameter of the resin particles.

[0408] The coefficient of variation is a value obtained by dividing the standard deviation of the number-based particle diameters obtained by the above-mentioned measurement by the number average particle diameter.

[0409] (2) Observation of particle shape

[0410] Fig. 4A is a SEM image of the hollow resin particles of Example II-1. Fig. 4B is a SEM image of a cross section of the hollow resin particles of Example II-1.

[0411] The observation conditions of SEM are as follows.

[0412] Scanning electron microscope:

[0413] Made by JEOL, Inc., Model: JSM-7610F (Figure 4A)

[0414] Made by Hitachi, Ltd., Model: S-4700 (Fig. 4B)

[0415] Accelerating voltage: 5.0 kV (Figure 4A, Figure 4B)

[0416] Magnification: 3000 times (Figure 4A), 2500 times (Figure 4B)

[0417] From these figures, it can be confirmed that the particles of Example II-1 are hollow inside and that, although hollow inside, they are not damaged and maintain a spherical shape.

[0418] (3) Measurement of the density of resin particles and calculation of the porosity

[0419] a. Determination of apparent density of resin particles

[0420] First, in the capacity of 100cm 3 Fill the volumetric flask to about 30 cm 3 The resin particles are placed in the volumetric flask and the mass of the filled resin particles is accurately weighed. Next, the volumetric flask filled with the resin particles is accurately filled with isopropyl alcohol up to the standard line, taking care not to introduce bubbles. The mass of the isopropyl alcohol added to the volumetric flask is accurately weighed, and the apparent density D1 (g / cm 3 ).

[0421] Formula (II)

[0422] Apparent density D1 = [mass of resin pellets] / (100 - [mass of isopropyl alcohol] ÷ [specific gravity of isopropyl alcohol at the measurement temperature])

[0423] b. Determination of true density of resin particles

[0424] After the resin particles are crushed in advance, the volume is 100cm 3 A volumetric flask is filled with about 10 g of crushed resin pellets, and the mass of the crushed pellets filled is accurately weighed.

[0425] Then, isopropyl alcohol was added to the volumetric flask in the same manner as in the measurement of the apparent density, and the mass of the isopropyl alcohol was accurately weighed. The true density D0 (g / cm 3 ).

[0426] Formula (III)

[0427] True density D0 = [mass of crushed resin pellets] / (100 - [mass of isopropyl alcohol] ÷ [specific gravity of isopropyl alcohol at the measurement temperature])

[0428] c. Calculation of void ratio

[0429] The void ratio (%) of the hollow resin particles can be calculated by the following formula (I) from the apparent density D1 and the true density D0 of the hollow resin particles.

[0430] Formula (I)

[0431] Void ratio (%) = 100 - (apparent density D1 / true density D0) × 100

[0432] (4) Volatile organic compound content of hollow resin particles

[0433] The method for determining the amount of volatile organic compounds contained in hollow resin particles is as follows. Add about 100 mg of hollow resin particles to a 30 mL screw-cap glass bottle and weigh accurately. Next, add about 10 g of tetrahydrofuran (THF) and weigh accurately. Stir the mixture in the glass bottle with a stirrer for 1 hour to extract the hydrocarbon solvent remaining inside the particles. Stop stirring, and after the resin component of the hollow resin particles that is insoluble in THF is precipitated, a filter (made by Advantech Co., Ltd., trade name: Membrane Filter 25JP020AN) is installed on a syringe, and the precipitate is filtered to obtain a sample solution, which is injected into a gas chromatograph (GC) for analysis. According to the peak area of ​​GC and the pre-made standard curve, the amount of volatile organic compounds per unit mass of the hollow resin particles (mass %) is calculated. The specific analysis conditions are as follows.

[0434] (Analysis conditions)

[0435] Apparatus: GC-2010 (manufactured by Shimadzu Corporation)

[0436] Column: DB-5 (manufactured by Agilent Technologies Inc.)

[0437] df=0.25μm 0.25mm ID×30m

[0438] Detector: FID

[0439] Carrier gas: nitrogen (linear velocity: 28.8 cm / sec)

[0440] Inlet temperature: 200℃

[0441] Detector temperature: 250°C

[0442] Oven temperature: increase from 40°C to 230°C at a rate of 10°C / min, and maintain at 230°C for 2 minutes.

[0443] Injection volume: 2 μL

[0444] (5) Evaluation of heat resistance of resin pellets

[0445] First, the resin pellets were heat treated by standing for 10 minutes in an electric furnace set at 200° C. Next, the resin pellets were taken out of the electric furnace and their apparent density was measured in the same manner as in the above “(3) Measurement of density of resin pellets and calculation of porosity”.

[0446] The apparent density of the resin particles after heat treatment is defined as D a The apparent density of the resin particles before heat treatment is set as D b , the density change rate d (%) was calculated based on the following formula (IV).

[0447] Formula (IV)

[0448] d={|D a -D b | / D b}×100

[0449] The smaller the density change rate d is, the smaller the influence of the heat treatment on the resin particles is, that is, the higher the heat resistance of the resin particles is.

[0450] The measurement and evaluation results of each resin pellet of Examples II-1 to II-4 and Comparative Examples II-1 to II-5 are shown in Table II-1 below. In Table II-1, "<1" indicates that the amount of volatile organic compounds is less than 1% by mass.

[0451] [Table II-1]

[0452]

[0453] II-3. Investigation

[0454] Hereinafter, the evaluation results of each resin pellet will be examined with reference to Table II-1.

[0455] According to Table II-1, the resin particles of Comparative Example II-1 are spherical. However, the residual hydrocarbon is as high as 30%, the solvent inside the particles is not fully removed, and the target hollow resin particles are not obtained. It can be considered that the reason is that when the total mass of at least one monomer selected from a monovinyl monomer and a hydrophilic monomer and a cross-linking monomer is taken as 100 parts by mass, the amount of cross-linking monomer added is as high as 65 parts by mass, so the degree of cross-linking is high and cyclohexane is difficult to penetrate. In the manufacturing method of Comparative Example II-1, the solvent removal process takes a long time, so it can be said that its productivity is low.

[0456] According to Table II-1, the resin particles of Comparative Example II-2 were damaged and irregular in shape. This is considered to be because the amount of the crosslinking monomer added was as small as 20 parts by mass when the total mass of at least one monomer selected from the monovinyl monomer and the hydrophilic monomer and the crosslinking monomer was taken as 100 parts by mass, so the degree of crosslinking was low, resulting in the particles not having the shell strength to withstand the temporary negative pressure inside the particles when the cyclohexane was removed.

[0457] According to Table II-1, the resin particles of Comparative Example II-3 are damaged and irregular in shape. Only resin particles with a porosity as low as 33% were obtained. Therefore, it can be seen that if solid-liquid separation is not performed to remove the cyclohexane contained in the particles in the aqueous medium, the resin particles will be damaged. The reasons can be speculated as follows. First, it can be considered that when cyclohexane is to be removed in the aqueous medium, water molecules outside the particles enter the inside of the particles to replace cyclohexane. In addition, water molecules further fill the free volume of the polymer that constitutes the shell of the particles. Therefore, it can be considered that the air permeability inside the polymer decreases. As a result, in the subsequent solvent removal process, air equivalent to the amount of water molecules that escaped to the outside of the particles did not enter the inside of the particles. Therefore, the hollow part cannot be maintained and the resin particles are damaged.

[0458] According to Table II-1, the resin particles of Comparative Example II-4 are spherical. However, the amount of volatile organic compounds is as high as 55% by mass, and the solvent inside the particles is not sufficiently removed, and the target hollow resin particles are not obtained. It is believed that since only a cross-linking monomer is used as a monomer, the degree of cross-linking is high and cyclohexane is difficult to penetrate. In the manufacturing method of Comparative Example II-4, since the solvent removal step takes a long time, it can be said that its productivity is low.

[0459] According to Table II-1, the density change rate d of the resin particles of Comparative Example II-5 after heat treatment is 87%, which is the highest among the resin particles in this experiment. Therefore, it can be seen that when no cross-linking monomer is used and acrylonitrile and methacrylonitrile are used in total at 95% by mass of the total monomers, heat treatment causes the porosity of the resin particles to drop sharply. It can be considered that this is because a cross-linking monomer that imparts heat resistance to the shell of the resin particles is not used, but a large amount of heat-sensitive acrylonitrile and methacrylonitrile are used instead, resulting in poor heat resistance of the obtained resin particles.

[0460] On the other hand, according to Table II-1, in the hollow resin particles of Examples II-1 to II-4, the amount of volatile organic compounds is as small as less than 1% by mass, and they are spherical, with a porosity of more than 75%, and the density change rate d after heat treatment is as low as less than 5%.

[0461] Therefore, it can be proved that by using the above-mentioned materials, preparing a mixed liquid, a suspension, and a precursor composition in sequence, and after solid-liquid separation of the obtained precursor composition, removing the hydrocarbon solvent contained in the precursor particles, it is possible to manufacture hollow resin particles with a higher porosity and excellent heat resistance than the prior art with high productivity.

[0462] Description of Reference Numerals

[0463] 1: Water-based medium;

[0464] 2: Low polarity materials;

[0465] 3: Suspension stabilizer;

[0466] 4: Monomer composition;

[0467] 4a: Monomer dispersed in aqueous medium;

[0468] 5: Oil-soluble polymerization initiator;

[0469] 6: Shell;

[0470] 7: Hydrocarbon solvents;

[0471] 8: Hollow part;

[0472] 10: micelle;

[0473] 13: Grease;

[0474] 14: Shell defect;

[0475] 20: precursor particles;

[0476] 51: Aqueous medium;

[0477] 52: surfactant;

[0478] 53: Monomer composition;

[0479] 53a: Monomer dissolved into aqueous medium;

[0480] 54: water-soluble polymerization initiator;

[0481] 60: micelle;

[0482] 60a: micelle precursor;

[0483] 61: core resin particles;

[0484] 62: Shell;

[0485] 63: hollow core;

[0486] 64: hollow part;

[0487] 100A: latex particles having a hollow portion;

[0488] 100B: latex;

[0489] 100C: hollow resin particles;

[0490] 200B: core-shell particles;

[0491] 200C: Hollow particles.

Claims

1. A method for producing hollow resin particles, characterized in that: The process includes the following steps: a step of preparing a mixed solution, wherein the mixed solution comprises at least one monomer selected from acrylic monovinyl monomers and acrylic hydrophilic monomers, a crosslinking monomer, an oil-soluble polymerization initiator, a hydrocarbon solvent, a suspension stabilizer, and an aqueous medium, wherein the acrylic monovinyl monomer is selected from methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and glycidyl (meth)acrylate, the acrylic hydrophilic monomer is selected from acrylic acid and methacrylic acid, the crosslinking monomer is selected from at least one of divinylbenzene, diallyl phthalate, allyl (meth)acrylate, and ethylene glycol di(meth)acrylate, and when the total mass of the monomers selected from the acrylic monovinyl monomers and the acrylic hydrophilic monomers and the crosslinking monomer is taken as 100 parts by mass, the content of the crosslinking monomer is 25 to 59 parts by mass, and the mass ratio of the acrylic hydrophilic monomer to the acrylic monovinyl monomer is 100:0 to 30:70; A step of preparing a suspension in which monomer droplets containing a hydrocarbon solvent are dispersed in an aqueous medium by suspending the mixed solution; A step of subjecting the suspension to a polymerization reaction to prepare a precursor composition containing precursor particles having a hollow portion and containing a hydrocarbon solvent; A step of obtaining the precursor particles by subjecting the precursor composition to solid-liquid separation; as well as A step of removing the hydrocarbon solvent contained in the precursor particles in a gas phase to obtain hollow resin particles having a porosity of 74% to 99%.

2. The manufacturing method according to claim 1, characterized in that: The method for separating the precursor composition into solid and liquid is centrifugal separation or filtration.

3. The manufacturing method according to claim 1 or 2, characterized in that: The process of preparing the mixed solution is a process of mixing an oil phase and an aqueous phase. The oil phase comprises at least one monomer selected from acrylic monovinyl monomers and acrylic hydrophilic monomers, a crosslinking monomer, an oil-soluble polymerization initiator and a hydrocarbon solvent, the acrylic monovinyl monomer being selected from methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate and glycidyl (meth)acrylate, the acrylic hydrophilic monomer being selected from acrylic acid and methacrylic acid, the crosslinking monomer being selected from at least one monomer selected from divinylbenzene, diallyl phthalate, allyl (meth)acrylate and ethylene glycol di(meth)acrylate, and, when the total mass of the monomers selected from the acrylic monovinyl monomers and the acrylic hydrophilic monomers and the crosslinking monomer is taken as 100 parts by mass, the content of the crosslinking monomer is 25 to 59 parts by mass, and the mass ratio of the acrylic hydrophilic monomer to the acrylic monovinyl monomer is 100:0 to 30:70, The water phase includes the suspension stabilizer and an aqueous medium.

4. The manufacturing method according to claim 1 or 2, characterized in that: At 20° C., the hydrocarbon solvent has a relative dielectric constant of 3 or less.

5. The manufacturing method according to claim 1 or 2, characterized in that: The hydrocarbon solvent is a hydrocarbon compound having 5 to 7 carbon atoms.

6. The manufacturing method according to claim 1 or 2, characterized in that: The hydrocarbon solvent is 200 parts by mass or more based on 100 parts by mass of the total mass of the at least one monomer selected from the monovinyl monomer and the hydrophilic monomer and the crosslinking monomer.

7. The manufacturing method according to claim 1 or 2, characterized in that: The obtained hollow resin particles have a number average particle size of 0.1 to 10 μm.

Citation Information

Patent Citations

  • Production of hollow polymer particle

    JP1986087734A

  • Polymer particle having internal hole and its production

    JP1987127336A

  • Production of hollow polymeric granule

    JP1994248012A

  • Hollow spherical organic pigment

    JP1999349839A

  • Hollow polymer fine particle and method for producing the same

    JP2002080503A